Graphene-supported CoS2 particles: an efficient photocatalyst for selective hydrogenation of nitroaromatics in visible light. Issue 13 (2nd June 2017) - Ma, Ben; Wang, Yingyong; Tong, Xili; Guo, Xiaoning; Zheng, Zhanfeng; Guo, Xiangyun
Abstract : CoS2 /graphene catalyst shows excellent photocatalytic performance for selective hydrogenation of nitroaromatics using molecular hydrogen as reducing agent under visible light. Abstract : CoS2 /graphene composites fabricated by a facile hydrothermal method exhibit excellent photocatalytic performance for selective hydrogenation of nitroaromatics to the corresponding aniline employing molecular hydrogen as a reducing agent under visible light irradiation (400–800 nm). The rate constant of the composite catalyst for nitrobenzene hydrogenation can achieve as high as 35.50 × 10 −3 min −1 with a selectivity of 100% toward the target product under mild conditions (30 °C and 0.25 MPa pressure of H2 ). The catalyst also shows high recyclability, and there is no decrease in the catalytic activity after five successive cycles. There exists a synergistic effect between the graphene support and the CoS2 particles: conductive graphene as the support can rapidly extract the photoexcited electrons and effectively suppress the recombination of photogenerated charges in CoS2 particles, and then improve the photocatalytic performance. The photocatalytic reduction of nitrobenzene over the CoS2 /graphene catalyst to aniline occurs through the direct pathway in the presence of H2 .